Emerging Radionuclides in a Regulatory Framework for Medicinal Products – How Do They Fit? - Decristoforo, Clemens; Neels, Oliver; Patt, Marianne (Frontiers in Medicine, 2021)
Recent years have seen the establishment of several radionuclides as medicinal products in particular in the setting of theranostics and PET. [177Lu]Lutetium Chloride or [64Cu]Copper Chloride have received marketing authorization as radionuclide precursor, [68Ga]Gallium Chloride has received regulatory approval in the form of different 68Ge/68Ga generators. This is a formal requirement by the EU directive 2001/83, even though for some of these radionuclide precursors no licensed kit is available that can be combined to obtain a final radiopharmaceuticals, as it is the case for Technetium-99m. In view of several highly promising, especially metallic radionuclides for theranostic applications in a wider sense, the strict regulatory environment poses the risk of slowing down development, in particular for radionuclide producers that want to provide innovative radionuclides for clinical research purposes, which is the basis for their further establishment. In this paper we address the regulatory framework for novel radionuclides within the EU, the current challenges in particular related to clinical translation and potential options to support translational development within Europe and worldwide.